1995
DOI: 10.1016/1074-7613(95)90048-9
|View full text |Cite
|
Sign up to set email alerts
|

Memory B cells from human tonsils colonize mucosal epithelium and directly present antigen to T cells by Rapid Up-Regulation of B7-1 and B7-2

Abstract: Human memory B cells that carry mutated IgV region genes were isolated from tonsils by negative selection of IgD+ naive B cells and CD38+ germinal center B cells and plasma cells. They were mainly found within the intraepithelial areas, but not in the B cell follicles of human tonsils. Memory B cells but not naive B cells have the capacity to present antigen directly to T cells, owing to the constitutive expression of the accessory molecules B7-1/CD80 and B7-2/CD86. Signals through antigen receptors and CD40 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
280
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(308 citation statements)
references
References 50 publications
27
280
0
1
Order By: Relevance
“…1). Phenotypically, these B cells were identical to the memory B cells of the tonsillar SE area described previously (25,35) and will be referred to as activated SE B cells.…”
Section: Hcdr3 Analysismentioning
confidence: 52%
“…1). Phenotypically, these B cells were identical to the memory B cells of the tonsillar SE area described previously (25,35) and will be referred to as activated SE B cells.…”
Section: Hcdr3 Analysismentioning
confidence: 52%
“…In contrast, the CD38 Ϫ ISCs, being CD40L dependent, will only survive and contribute Ig as long as Ag and T cell help are both available. Given that stimulation of activated T cells requires Ag presentation by memory B cells (1,42), successful Ag clearance would act as a feedback mechanism limiting memory B cell expansion and further development of both short-and long-lived ISCs, although limited differentiation of the CD38 ϩ ISCs already formed would continue. In vivo studies have revealed that the number of Ag-specific B cells present at the conclusion of a secondary immune response is reduced 10-to 50-fold compared with the peak of the response, indicative of apoptosis of the majority of memory blasts after Ag clearance (12).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding was the demonstration of 5-to 30-fold more IgM, IgG, and IgA secreted by memory compared with naive B cells under these stimulation conditions (Table I). The CD38 ϩ cells generated in these cultures displayed reduced expression of CD20, but maintained high levels of CD39 (data not shown), thereby distinguishing them from GC B cells (17,42).…”
Section: Il-10 Promotes Cd40l-stimulated Memory But Not Naive B Celmentioning
confidence: 99%
“…Phenotypically distinct subsets of human B cells can also be identified in different lymphoid tissues. Thus, immature B cells are CD19 ϩ CD27 Ϫ CD10 ϩ IgM ϩ IgD Ϫ , while naive B cells are CD19 ϩ CD27 Ϫ IgM low IgD high , and memory B cells are CD19 ϩ CD27 ϩ and express IgM, IgG, or IgA (2,(12)(13)(14)(15). Human transitional B cells, however, remain poorly characterized, although their existence is suggested by the recent demonstration of a population of cells in peripheral blood (PB) distinguishable from mature B cells on the basis of a CD24 high CD38 high phenotype (16,17).…”
mentioning
confidence: 99%